1998
DOI: 10.1137/s0036142997317560
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Nonoscillatory Central Schemes with Nonstaggered Grids for Hyperbolic Conservation Laws

Abstract: We present a general procedure to convert schemes which are based on staggered spatial grids into nonstaggered schemes. This procedure is then used to construct a new family of nonstaggered, central schemes for hyperbolic conservation laws by converting the family of staggered central schemes recently introduced in [H. Nessyahu and E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
169
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(171 citation statements)
references
References 29 publications
1
169
0
Order By: Relevance
“…In order to test our schemes in practice, we compared them with two other schemes, the first order Engquist-Osher scheme proposed in [6] and a central scheme which is an adaptation of schemes presented in [10]. We have no convergence proofs for these schemes.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…In order to test our schemes in practice, we compared them with two other schemes, the first order Engquist-Osher scheme proposed in [6] and a central scheme which is an adaptation of schemes presented in [10]. We have no convergence proofs for these schemes.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…This is of importance for a construction of higher-order non-staggered central schemes which does not follow the mentioned recipe presented in [7]. The construction of such schemes is surely an issue for future developments because non-staggered grids are advantageous if complex geometries and boundary conditions come into play.…”
Section: Conclusive Remarksmentioning
confidence: 99%
“…The investigations within this paper show, that one needs to be very careful when constructing a central scheme, especially on a non-staggered grid. One may understand some parts of our investigations as a justification of the approach presented in [7]: there, non-staggered central schemes are derived by integration using staggered grids followed by an averaging projection onto the initial non-staggered cells.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang, et al [14] later extended the NT algorithm to multiple space dimensions and demonstrated that the central scheme does not require a spatial splitting. Subsequently, Jiang, et al [14] introduced a non-staggered central scheme that retains the "Riemann-solver-free" aspect of the original staggered NT algorithm.…”
Section: Central Schemesmentioning
confidence: 99%
“…Subsequently, Jiang, et al [14] introduced a non-staggered central scheme that retains the "Riemann-solver-free" aspect of the original staggered NT algorithm. Here, it was first suggested that central schemes could form the basis for a robust generalized computational framework for systems of conservation laws.…”
Section: Central Schemesmentioning
confidence: 99%